2020
DOI: 10.2478/johr-2020-0008
|View full text |Cite
|
Sign up to set email alerts
|

Control of Root-Knot Nematode (Meloidogyne incognita) in Tomato (Solanum lycopersicum) Crop Using Siam Weed (Chromolaena odorata) Compost Manure

Abstract: A field experiment was conducted at Landmark University Omu-Aran, Nigeria from June to November 2017 and repeated at the same time in the year 2018 on a nematode infested soil to evaluate the effects of different amounts of Siam weed compost on the performance of root-knot nematode (RKN) infested tomato. The compost was applied a week before planting as soil amendment at the amount of 0.0, 0.5, 1.5, and 2.0 t·ha−1, while carbofuran was applied at the rate of 3.0 kg·ha−1. Four weeks old tomato seedlings cultiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The ethnomedicinal, antimicrobial, and phytochemical properties of banana, plantain, and bitterleaf are widely known; however, the drawbacks from the environmental associations in which they are grown make them unhealthy and a threat to consumers along the food chain [5], [6], [11]. Active points of production that chiefly release hazardous pollutants in the area include paint and lubricant, road tar, oil sludge, petroleum wastes with limitless transmission facilities, a seaport [2], etc.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ethnomedicinal, antimicrobial, and phytochemical properties of banana, plantain, and bitterleaf are widely known; however, the drawbacks from the environmental associations in which they are grown make them unhealthy and a threat to consumers along the food chain [5], [6], [11]. Active points of production that chiefly release hazardous pollutants in the area include paint and lubricant, road tar, oil sludge, petroleum wastes with limitless transmission facilities, a seaport [2], etc.…”
Section: Resultsmentioning
confidence: 99%
“…Assessing the likelihood of neurological and death-trap sickness and diseases caused upon consuming V. amygdalina and Musa sp. from previous research [5], [3]- [6], reveals loopholes in health infrastructure programs as well as the potency of these pollutants to cause outbreaks of infectious diseases in oil-rich areas like Koko.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Summers (2011) observed that application of organic manure helps to control the incidence of parasitic nematodes by promoting the multiplication of micro-organisms (fungi & bacteria) therefore improve the growth and yields of crop. Abolusoro et al (2013) reported that application of poultry manure, domestic waste, cow dung and inorganic fertilizers helped to decrease the incidence of nematodes and enhance the growth of eggplant. Kumar & Sharma (2006) recorded highest shoot & root length, maximum fresh & dry shoot & root weight and maximum number of fruits per plant with the application of Glomus fasciculatum at nursery stage of tomato.…”
Section: Response On Diseases and Pestsmentioning
confidence: 99%
“…Phytotoxicity, environmental pollution and nematode resistance result from the indiscriminate use of synthetic pesticides for controlling nematodes (Yudelman et al, 1998;Pandey, 2005;Thligene et al, 2019). Compounds that occur naturally are usually inexpensive, easy to apply and do not pollute the environment and have potential to replace synthetic nematicides (Burow et al, 2007;Abolusoro et al, 2020;Favaz et al, 2021;Okechalu et al, 2021;Samara, 2022;Mamman et al, 2022).…”
Section: Introductionmentioning
confidence: 99%